2003
DOI: 10.1046/j.1463-1326.2003.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adiponectin in overweight, nondiabetic individuals with or without insulin resistance

Abstract: This study shows that adiponectin is an important molecular link between obesity, insulin resistance and atherogenic lipoproteins. It is possible that plasma adiponectin concentration may be a convenient marker for identifying subjects with the metabolic syndrome who may progress to impaired glucose tolerance. Longitudinal studies are required in order to verify this clinical application of adiponectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
5
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 11 publications
10
57
5
9
Order By: Relevance
“…14,25 Adiponectin has several advantages as a marker of IR, as we have shown previously that this relationship is independent of body weight and adiposity, 16 whereas this study shows that low circulating levels of adiponectin precede the development of IFG. In comparison, changes in IR indices, derived from insulin and glucose concentrations, seem to occur later in the progression of the disease and are known to be more influenced by confounding factors, such as anthropometry and variability in fasting conditions and sample collection.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…14,25 Adiponectin has several advantages as a marker of IR, as we have shown previously that this relationship is independent of body weight and adiposity, 16 whereas this study shows that low circulating levels of adiponectin precede the development of IFG. In comparison, changes in IR indices, derived from insulin and glucose concentrations, seem to occur later in the progression of the disease and are known to be more influenced by confounding factors, such as anthropometry and variability in fasting conditions and sample collection.…”
Section: Discussioncontrasting
confidence: 41%
“…10 More recently, an index incorporating fasting insulin and triglyceride levels, the McAuley index, has also been shown to be a sensitive marker of IR 11 and has attracted increasing use in clinical research. The presence of the metabolic syndrome (MetS) itself is also often used as a surrogate marker of IR, 12 with its characteristic abnormalities of a raised triglyceride (trig) to highdensity lipoprotein (HDL)-cholesterol ratio (trig:HDL) 13 and low circulating levels of the insulin-sensitizing adipocytokine, adiponectin, [14][15][16] shown to correlate with the degree of IR.…”
Section: Introductionmentioning
confidence: 99%
“…Correlations between HOMA and serum adiponectin and subcutaneous mRNA levels have been reported previously. 30,40,41 Motoshima et al 22 showed that adiponectin secretion was higher from cultured human omental than from subcutaneous adipocytes. In the same study, they also showed that omental adiponectin secretion was increased after insulin treatment while subcutaneous secretion was unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…That patients with obesity, hypertension, coronary artery disease (CAD), diabetes on the cusp of inflammation, and insulin resistance are associated with hypoadiponectinemia supports this speculation. [19,24,25] Although plasma adiponectin concentrations are higher in patients with ESRD than in healthy subjects, the kidney's role in the metabolism of adiponectin is unknown. [8] Guebre et al has suggested that plasma adiponectin concentrations in chronic kidney disease are related more to metabolic disturbances than to decline in renal function.…”
Section: Tablementioning
confidence: 99%